2018
DOI: 10.1186/s13018-018-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

The distance of the femoral neurovascular bundle from the hip joint: an intraoperative guide to reduce iatrogenic injury

Abstract: BackgroundIatrogenic injury to the femoral neurovascular bundle is not uncommon during primary and revision total hip replacement (THR) and can result in permanent weakness, pain and poor function. Prevention of injury to these structures relies on a sound knowledge of their relationships to the hip joint.MethodsWe studied 115 consecutive hip magnetic resonance imaging (MRI) results in order to identify objective relationships between these structures and the hip joint that can be used intraoperatively.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…At the 3 or 9 o'clock position, an almost similar level as the point of 90°, the mean distance to the femoral nerve ranged from 18.0 mm to 23.6 mm. 10,12,1719 In the present study, the mean distance to the femoral nerve from the 90° point of the anterior acetabulum was 21.1 ± 7.4 mm. This result is consistent with data from previous studies.…”
Section: Discussionsupporting
confidence: 48%
“…At the 3 or 9 o'clock position, an almost similar level as the point of 90°, the mean distance to the femoral nerve ranged from 18.0 mm to 23.6 mm. 10,12,1719 In the present study, the mean distance to the femoral nerve from the 90° point of the anterior acetabulum was 21.1 ± 7.4 mm. This result is consistent with data from previous studies.…”
Section: Discussionsupporting
confidence: 48%
“…In addition to the relative relationship between the femoral head and the acetabulum, other factors may affect the distance between the neurovascular bundle and hip joint. Mehta et al found that patients with a low body weight may be at a higher risk of iatrogenic injury due to the reduced distance of the neurovascular structures to the hip [ 25 ]. The children in this study are only one to two years old and thus obviously weigh less than adults, and this will cause the neurovascular bundle to be closer to the hip capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on peripheral nerve anatomy and course were mainly based on magnetic resonance imaging (MRI) or cadaveric specimens. However, CT might be a better choice of evaluating nerve course for DDH [20][21][22][23][24][25]. On the one hand, MRI was not a routine examination for DDH patients and cannot clearly show bony landmarks; it would increase patients' medical costs purely for the purpose of observing nerve course.…”
Section: Discussionmentioning
confidence: 99%